WIDE DISTRIBUTED ARTIFICIAL WATER BASIN IN KHURASON AND MOVAUNNAHR COUNTRIES - To’rayeva Nilufar Nortoji qizi; Abdullayev Azimjon Karim o’g’li (Galaxy International Interdisciplinary Research Journal, 2023)
Natural solar heat, water supply.